Estudo fitoquímico e análise biológica/farmacológica de Bredemeyera floribunda Willd - Cavalcante, Gizely de Vasconcelos Leite (2015)
Some plant species are used in folk medicine to treat accidents with poisonous animals. The species Bredemeyera floribunda Willd (Polygalaceae), popularly known as "snake root" has this popular use. In addition to its anti-snake venom properties, the species is also known for its expectorant, diuretic and hypotensive properties. Due to its ethnopharmacological importance, this species still needs chemical studies. This work reports the phytochemical study from roots of the B. floribunda. Were performed analysis using chromatographic techniques: High Performance Liquid Chromatography, Adsorption Chromatography and Molecular Exclusion Chromatography. Chromatographic fractionation from ethanolic extract of the roots of B. floribunda resulted in the isolation of seven substances, the first being a derivative of cinnamic acid, known as (2E)-methyl-3-(3,4,5-trimethoxyphenyl)-prop-2-enoate, unpublished in the Bredemeyera genus, flavonoid rutin and three xanthones, the first called 1,7-dihydroxy3,4,8-trimethoxy-xantone, the second, 1,3,7-trihydroxy-4,8-dimethoxy-xanthone, and a third dimethoxyl-xanthone, possibly not previously report in the literature. Were isolated also the sucrose and a derivative bicyclic of mannitol. Furthermore, saponines have also been identified. The structural determination of secondary metabolites was performed by nuclear magnetic resonance 1H and 13C, using 1D and 2D pulse sequences and comparison with the literature data. Some isolated compounds, fractions, and the ethanol extract were subjected to hemorrhagic and proteolytic assays. In these tests, it was observed that the extract showed to be active and which of the tested substances, xanthones 1,3,7-trihydroxy-4,8-dimetoxyxanthone and 1,7-dihydroxy-3,4,8-obtained results trimethoxy-xanthone satisfactory. Fractions containing xanthones and saponins also were submitted to the tests and showed promising results.